2012
DOI: 10.1007/s10865-012-9424-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of conditioned pain modulation in humans by naltrexone: an exploratory study of the effects of pain catastrophizing

Abstract: The current study tested the hypothesis that conditioned pain modulation is mediated by the release of endogenous opioids with a placebo-controlled (sugar pill) study of naltrexone (50 mg) in 33 healthy volunteers over two counter-balanced sessions. Pain modulation consisted of rating of heat pain (palm) during concurrent cold water immersion (foot). Compared to baseline heat pain ratings, concurrent foot immersion lowered pain intensity ratings, which suggests an inhibitory effect, was reduced with naltrexone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 83 publications
(131 reference statements)
5
86
0
2
Order By: Relevance
“…51 However, the present findings indicate that additional opioid receptor blockade masked the analgesic response, thus supporting the view that opioid peptides play a primary role not only in the generalized form of conditioned pain modulation 18,30,32,35,38,54 but also in the lateralized type.…”
Section: Pain Ratings To Electrical Stimulation Of the Forearm Duringsupporting
confidence: 72%
See 1 more Smart Citation
“…51 However, the present findings indicate that additional opioid receptor blockade masked the analgesic response, thus supporting the view that opioid peptides play a primary role not only in the generalized form of conditioned pain modulation 18,30,32,35,38,54 but also in the lateralized type.…”
Section: Pain Ratings To Electrical Stimulation Of the Forearm Duringsupporting
confidence: 72%
“…We also investigated the effect of combined opioid receptor and α 2 -adrenoceptor blockade on pain ratings to electrical stimulation of the HFS-treated site in the forearm during and after painful stimulation of each temple. As opioid peptides contribute to conditioned pain modulation, 18,30,32,35,38,54 we hypothesized that opioid receptor blockade would inhibit the ipsilateral component of this response despite an opposing effect of yohimbine. 51…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Animal models and human studies suggest that the CPM is greatly dependent on the integrity of endogenous opioid (21) and descending bulbospinal serotonergic systems (6). Most recently, King and colleagues found that the administration of an opioid antagonist blocked the inhibition of focal heat pain of the palm during cold water immersion of the foot (21). Animal studies show that regular physical exercise increases endogenous opioid content in the central nervous system (e.g., cerebrospinal fluid and brainstem; 34) and the availability of serotonin in the brain (1).…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting data on the effect of naloxone/naltrexone on CPM as some found inhibition of CMP (Pertovaara et al, 1982;Willer et al, 1990;King et al, 2013a) whereas others found no effect (Peters et al, 1992;Edwards et al, 2004;Sprenger et al, 2011).…”
Section: Targeting Descending Pathwaysmentioning
confidence: 99%